Death and anti-death: tumour resistance to apoptosis - Igney, Frederik; Krammer, Peter H. (Nature reviews. Cancer, 2002)
Apoptosis is a multi-step, multi-pathway cell-death programme that is inherent in every cell of the body. In cancer, the apoptosis:cell-division ratio is altered, which results in a net gain of malignant tissue. Apoptosis can be initiated either through the death-receptor or the mitochondrial pathway. Caspases that cleave cellular substrates leading to characteristic biochemical and morphological changes are activated in both pathways. The apoptotic process is tightly controlled by various proteins. There are also other caspase-independent types of cell death. Many physiological growth-control mechanisms that govern cell proliferation and tissue homeostasis are linked to apoptosis. Therefore, resistance of tumour cells to apoptosis might be an essential feature of cancer development. Immune cells (T cells and natural killer cells) can kill tumour cells using the granule exocytosis pathway or the death-receptor pathway. Apoptosis resistance of tumour cells might lead to escape from immunosurveillance and might influence the efficacy of immunotherapy. Cancer treatment by chemotherapy and γ-irradiation kills target cells primarily by inducing apoptosis. Therefore, modulation of the key elements of apoptosis signalling directly influences therapy-induced tumour-cell death. Tumour cells can acquire resistance to apoptosis by the expression of anti-apoptotic proteins or by the downregulation or mutation of pro-apoptotic proteins. Alterations of the p53 pathway also influence the sensitivity of tumour cells to apoptosis. Moreover, most tumours are independent of survival signals because they have upregulated the phosphatidylinositol 3-kinase (PI3K)/AKT pathway. The present aim of research in this area is to understand further the molecular mechanisms of tumour resistance and sensitivity, and to use this insight to resensitize tumour cells to apoptosis and, accordingly, to tumour therapy.
Gesehen am 02.03.2021